Implementasi Pemberian Jus Wortel Terhadap Penurunan Tekanan Darah Untuk Penderita Hipertensi Pada Lansia Di Panti Sosial Tresna Werdha Pagar Dewa Bengkulu Tahun 2025 - Rahmadani, Ienes Dwi; Arfianti, Mariza; Aprianti , Delta (Jurnal Pakar Kesehatan, 2025)
According to the World Health Organization, 1.56 billion people will be living with hypertension by 2025, and approximately 9.4 million deaths occur each year. In Indonesia, the prevalence reaches 34.1%, and in Bengkulu Province, it increases to 32.83%. At Tresna Werdha Pagar Dewa Social Home in Bengkulu City, the number of elderly people with hypertension continues to increase, namely 17 people (2022), 21 people (2023), and 23 people (2024). One potential non-pharmacological treatment method is the administration of carrot juice (Daucus carota L.), as it contains potassium, magnesium, and beta-carotene, which can help lower blood pressure. This study aims to determine the effect of carrot juice administration on lowering blood pressure in elderly people with hypertension. This study used a descriptive method with a case study approach. The research subject was a 73-year-old male elderly person with mild hypertension. The intervention was carried out by giving 200 ml of carrot juice every morning for 7 consecutive days. It was found that blood pressure before therapy was 149/94 mmHg, and then after 7 days of carrot juice administration, the patient's blood pressure decreased to 137/86 mmHg, showing a decrease of 12 mmHg systolic and 8 mmHg diastolic. In addition, the patient also experienced improvement in symptoms such as reduced dizziness and sleep disturbances. In conclusion, regular carrot juice administration is effective in lowering blood pressure in elderly individuals with mild hypertension. This therapy can serve as a non-pharmacological alternative.